Carbonate mineral precipitation induced by microorganisms enriched from the cave water and biofilm in a lime-decorated lava tube - Yumi Kim; Sung-min Kang; Kyoung-nam Jo; Yul Roh (Scientific Reports)
Abstract Cave microorganisms associated with calcareous speleothems have been reported to facilitate calcium carbonate precipitation through crystal nucleation and mineral growth. In this study, we used carbonate-forming microorganisms enriched from cave water droplets and stalactite biofilm samples to induce precipitation of Mg2+ or Sr2+-coprecipitated carbonate minerals and explored their mineralogical properties. The samples for these analyses were collected from Yongcheon Cave, a lime-decorated lava tube located on Jeju Island in South Korea. They included five soil and sediment samples from outside the cave, seven drip water samples from inside the cave, and nine biofilm samples swiped using sterilized cotton swabs from inside the cave. The microorganisms enriched from the drip water samples comprised bacterial genera, including Pseudomonas, Bacillus, Stenotrophomonas, Acinetobacter, and Morganella. which are known to contribute to carbonate formation. In contrast, the microorganisms enriched from the biofilms were dominated by Pseudomonas. When only Ca2+ was present in the growth medium (Ca:Sr = 3:0), these microorganisms precipitated calcite and vaterite. Conversely, when Ca2+ and Sr2+ were present at varying ratios (Ca:Sr = 2:1, 1:1, and 1:2), calcian-strontianite was precipitated. Furthermore, when only Sr2+ was present (Ca:Sr = 0:3), strontianite was formed. Adding Ca2+ and Mg2+ at varying ratios (Ca:Mg = 2:1, 1:1, and 1:2) led to the precipitation of magnesian-calcite and monohydrocalcite. When only Mg2+ was added to the medium (Ca:Mg = 0:3), nesquehonite and struvite precipitated. These findings suggest that microorganisms enriched from the lava tube cave induce calcium carbonate precipitation through ureolysis and that Sr/Cr and Mg/Ca ratios influence the type of precipitated carbonate or phosphate minerals.